Textbook of Biochemistry With Clinical Correlations - Devlin, Thomas M;Ed (WILEY-LISS, 2002)
Thomas Devlin presents the biochemistry of mammalian cells, relates events at the cellular level to the subsequent physiological processes in the whole animal, and cites examples of human diseases derived from aberrant biochemical processes.